2017
DOI: 10.5430/jha.v6n4p39
|View full text |Cite
|
Sign up to set email alerts
|

Impact of emotional intelligence coaching on job satisfaction of pharmacists during organizational changes

Abstract: Job satisfaction is known to decline during times of major organizational change and emotional intelligence has been positively correlated with job satisfaction and adaptability. Computerized provider order entry (CPOE), closed loop medication administration, electronic medication administration records and 24/7 pharmacy services were implemented at London Health Sciences Centre (LHSC) during the spring of 2014. This pilot randomized controlled trial assessed whether completion of an emotional intelligence ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…Similarly, in a 2022 study by Salmoneh that utilized quantitative and qualitative methods to measure the impact of factors such as a smart working environment, job security, and EI on employee satisfaction during COVID-19 in Jordanian pharmacies, it was found that pharmacists in community pharmacies in Amman acknowledged EI as a motivating factor contributing to job satisfaction [40]. Sub-dimensions of EI have been consistently associated with job satisfaction [41], and EI itself is positively correlated with job satisfaction [42,43].…”
Section: Relationship Between Emotional Intelligence With Job Satisfa...mentioning
confidence: 99%
“…Similarly, in a 2022 study by Salmoneh that utilized quantitative and qualitative methods to measure the impact of factors such as a smart working environment, job security, and EI on employee satisfaction during COVID-19 in Jordanian pharmacies, it was found that pharmacists in community pharmacies in Amman acknowledged EI as a motivating factor contributing to job satisfaction [40]. Sub-dimensions of EI have been consistently associated with job satisfaction [41], and EI itself is positively correlated with job satisfaction [42,43].…”
Section: Relationship Between Emotional Intelligence With Job Satisfa...mentioning
confidence: 99%
“…This, of course, needs emotional intelligence training and development for practitioners in the field of pharmacy (Higuchi et al 2017). Particularly, adaptability and flexibility in the emergent circumstances or during organizational change (Seymour et al 2017).…”
Section: Emotional Intelligence In Healthcarementioning
confidence: 99%
“…En un estudio realizado por Seymour (2017), se presentan resultados estadísticos que indican la afectación significativa en las competencias de la IE después de una intervención de coaching a 30 líderes, usando como herramienta la escala de Reuven Bar-On. La relevancia de este modelo se consolida por la necesidad de liderazgo efectivo en las organizaciones, que está respaldada por diversos estudios (Kotzé y Venter, 2011).…”
Section: La Inteligencia Emocionalunclassified
“…La intervención se diseñó con base en el modelo de coaching holístico de Seymour et al (2017), considerando las habilidades de la IE del modelo de Reuven Bar-on intituladas: Autoconcepto, Autorrealización, Autoconciencia emocional, Expresión emocional, Asertividad, Independencia, Relaciones interpersonales, Empatía, Responsabilidad social, Resolución de problemas, Evaluación de la realidad, Control de impuestos, Flexibilidad, Tolerancia al estrés, y Optimismo (Bar-On, 2006) de acuerdo con el modelo teórico postulado por Ugarriza (2001) y construido en consecuencia. Debido a que el interés en el estudio de estas variables ha crecido exponencialmente, pues se presume que las habilidades emocionales se convierten en una ventaja competitiva cuando el líder las desarrolla, se realizó este trabajo buscando que el resultado sea valioso para la empresa turística de la Riviera Maya al mostrar la preeminencia del coaching para el desarrollo de las habilidades emocionales y la herramienta de Reuven Bar-on para lograr mediciones certeras de la intervención.…”
Section: / 23unclassified